Erythropoietin attenuates renal and pulmonary injury in polymicrobial induced-sepsis through EPO-R, VEGF and VEGF-R2 modulation - Heitrich, Mauro Oscar (2016)
Fil: Heitrich, Mauro Oscar. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.